Overcoming the Male Leadership Culture. Issue 3 (12th November 2019) - Dove, Rick
ABSTRACT: Empowering women as leaders in systems engineering is a clarion call–a strong and emotional appeal to do something. But who is to do this empowering, why should it be done, and what stands in the way? This article speaks to both men and women, collectively and individually. For men that feel empathetic and supportive of gender equality, it will suggest why your empathy and support may not be what you think it is. For women who want to understand the nature of the inequality problem, it will show you key elements of what perpetuates it as a means to help address it. The principle goals of this article are to expose some key elements of the problem space, and to create an appreciation for the values of social sensitivity in working relationships and in leadership.